Analisis Tingkat Kemampuan Membaca dan Menulis Arab Melayu Mahasiswa S1 Kelas 2021 A Program Studi Pendidikan Bahasa dan Sastra Indonesia - Irma Alda Iryani; M. Zafran Syaira; Rani Alvira Aisyah; Muhammad Fajri; Nanda Rizka Pratama; Elza Nurman; Hasnah Faizah AR (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The study reviewed the level of ability to read and write Arab malays class 2021a Indonesian language and literature education course, riau university. The research method used by researchers is a descriptive quantitative approach. The data obtained came from the liquerskin fill-off results given to 34 of the research samples. The data-gathering technique used is charging the angketts using a Google form given online. The data was analysed with a few statistical steps, among them relative frequency distribution, normality test, and followed by the chi test of one sample. Based on analysis obtained, it is known that the average level of ability to read and write Arab malaws class 2021a program for language and literary education, riau university is 18.4 on reading and 18.65 on writing ability.